“THE IMPACT OF ONLINE EDUCATION ON TRADITIONAL SCHOOLING” (Zamonaviy dunyoda ijtimoiy fanlar, 2026)
This article analyzes the influence of online education on traditional schooling. It investigates both benefits and challenges of digital learning integration, examining effects on students’ academic performance, motivation, and social development. The study also discusses strategies for effectively combining online and traditional learning to create a balanced educational approach. Real-life examples, statistical data, and case studies are included to provide a comprehensive understanding of this transformation.